A journey through maps from the Ottoman world to the Republic of Turkey between the 15th and the 20th centuries : the cartographic collection of Erhan Öner - Öner, Erhan, 1946- (İstanbul)
4 c. (1. c. 456, [2] s. ; 2. c. 513, [1] s. ; 3. c. 468, [1] s. ; 4. c. 490, [1] s.)